2021
DOI: 10.1002/ps.6451
|View full text |Cite
|
Sign up to set email alerts
|

Power on! Low‐energy electrophysical treatment is an effective new weed control approach

Abstract: BACKGROUND Environmental concerns are driving the call for adoption of alternative nonchemical weeding approaches. This study aimed to develop and evaluate a novel, precise, low‐energy electrophysical treatment weeding systems and to provide new insight into their control mechanism. Two electrophysical treatment systems, based on AC (2.2 kV) and DC (40 kV) energy sources, were developed and evaluated. The impacts of various operational and biological factors on the weed control effectiveness were evaluated. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Effects are influenced by the voltage and length of the current application and may be altered by the thermal tolerance and moisture content of the soil biota. A recent study by Lati et al (2021) found that an application of 0.05 Wh with experimental continuous-contact machinery could result in a >40 C increase in the temperature of A. retroflexus , S. nigrum , and johnsongrass [ Sorghum halepense (L.) Pers.]. Therefore, it stands to reason that if such large changes are observed in the temperature of the plant shoots, there may be a change in the root and soil temperatures that affects the soil biological population.…”
Section: Ecological Impacts Of Electric Weed Controlmentioning
confidence: 97%
See 2 more Smart Citations
“…Effects are influenced by the voltage and length of the current application and may be altered by the thermal tolerance and moisture content of the soil biota. A recent study by Lati et al (2021) found that an application of 0.05 Wh with experimental continuous-contact machinery could result in a >40 C increase in the temperature of A. retroflexus , S. nigrum , and johnsongrass [ Sorghum halepense (L.) Pers.]. Therefore, it stands to reason that if such large changes are observed in the temperature of the plant shoots, there may be a change in the root and soil temperatures that affects the soil biological population.…”
Section: Ecological Impacts Of Electric Weed Controlmentioning
confidence: 97%
“…Applicators can also be adapted to function at a greater or lesser height above the ground or by increasing the electrode's effective contact surface to target shorter or taller weeds and instances of greater branching. For example, Lati et al (2021) found that with applications by either spark-discharge or continuous contact (prototype machinery), greater efficacy was achieved when the current (0.16 Wh) was applied to the youngest fully emerged leaf, rather than the middle part of the plant stem. Therefore, while electric weed control represents a possible solution for current herbicide-resistance issues, research is required to determine the ability of weeds to adapt to its potential uses.…”
Section: Potential Application Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…The technology was investigated in sugar beets ( Beta vulgaris L.) in the 1970s (Diprose et al 1985; Rasmusson et al 1980; Vingneault and Benoît 2001), and there has recently been renewed interest, likely due to the increase in herbicide-resistant weeds (Heap 2023) and the development of new electrical weeding machines (Bloomer et al 2022; Lati et al 2021; Lehnhoff et al 2022). The flow of electricity through a plant generates heat, which causes water molecules inside the plant vasculature to vibrate at a high intensity, resulting in damage to cell walls and destruction of tissues, ultimately leading to plant death (Lati et al 2021; Vingneault and Benoît 2001). Several studies have documented effective electric suppression of weeds under laboratory conditions (Bloomer et al 2022; Lati et al 2021; Lehnhoff et al 2022; Şahin and Yalınkılıc 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Most recent literature on using electricity for weed control focuses on lethal deliveries of electrical energy in a relatively short time (Diprose et al, 1984; Sahin, 2020; Sahin and Yalınkılıc, 2017) or the production of microwaves, which can be energetically inefficient but effective (Diprose et al, 1984; Sartorato et al, 2006). Little attention is given to the potential of using small currents applied in long‐term control settings, although Lati et al, 2021 demonstrated that 2.2 kV (AC) and 40 kV (DC) were capable of damaging plants. With the use of current controlling semiconductor circuits these issues of safety and energy use can be managed.…”
Section: Introductionmentioning
confidence: 99%